SISTEM KEWARISAN MENURUT HUKUM ADAT MASYARAKAT SUKU TALANG MAMAK - Erdiansyah Erdiansyah; Hengki Firmanda; Nurahim Rasudin (Fakultas Hukum Universitas Riau, 2021)
The customary legal system of the Mamak Tribe community with a matrilineal kinship system. The division of the inheritance system according to the customary law of the talak mamak tribe adheres to the matrilineal system and the combination between the individual inheritance system and the collective inheritance system. The division of inheritance is done by ninik mamak of the heirs. First, high estate, low estate (livelihood / livelihood) should be separated from the property of the husband and wife, after which the division of this inheritance property can be distributed to the heirs. When a dispute arises, it is first resolved as a family through deliberation. Dispute Resolution on the Rights of the Mamak Tribe Women According to the Dispute over the rights of the Mamak Tribe Women will be brought to a deliberation within the Talang Mamak Tribunal if no agreement is found in the family, then a resolution is requested in the Mamak Tribal Tribal Customs procedure. The parties involved in resolving the dispute over the women's rights of the Talang Mamak Tribe include: the Head of the Tribe, as well as all the customary leaders in the institution.